Fault-tolerant analysis and control of SSRMS-type manipulators with single-joint failure. (March 2016) - She, Yu; Xu, Wenfu; Su, Haijun; Liang, Bin; Shi, Hongliang
Abstract: Several space manipulators, whose configurations are similar to that of the Space Station Remote Manipulator System (SSRMS, also called Canadarm2), are playing important roles in the construction and maintenance of the International Space Station. Working in the harsh orbital environment, they are at high risk of single-joint failure. Fault-tolerant capability is critical for those manipulators to complete their on-orbital tasks. In this paper, we analysed and compared the manipulation capability of SSRMS-type manipulators with joints locked at arbitrary positions, and proposed efficient path planning via a fault-tolerant control method. First, a unified kinematic model of this type of manipulators was established. Second, the manipulation capability of the original 7-DOF (degrees of freedom) redundant manipulator was analysed and compared with its degraded 6-DOF counterparts formed by different joint locking configurations. Then, we identified those joints with large sensitivity to fault tolerance performance. The influences of different positions of all joints were also determined by numerical computation. Based on the analysis, the relatively safe and dangerous regions for each joint failure were identified. Finally, we proposed a path planning strategy and realized by a H∞ controller which enables the failure joint locked in the safe region, and simulations were carried on a degraded 3-DOF planar redundant manipulator to verify the planning strategy and control approach. This paper provided important analysis results and efficient methods to address the possible problems of SSRMS-type manipulators caused by single-joint failure that can be extended to other types of manipulators. Moreover, the proposed method is useful for designing the optimal configuration of a redundant manipulator. Highlights: Unified kinematics modelling of SSRMS-type manipulators. Important fault-tolerant criteria defined to measure the fault-tolerance. Fault-tolerant analysis for SSRMS manipulator with single joint failure. Identification of the safe and dangerous regions for each joint failure. Efficient fault-tolerant path planning and H∞ control methods.